Pelatihan Dan Penampingan Pengolahan Rumput Laut Dan Hasil Laut Menjadi Aneka Kuliner Pada Nelayan di Desa Labuhan Haji Kabupaten Lombok Timur - Sulaimiah Sulaimiah; Santi Nururly; Sulhaini Sulhaini (Jurnal Gema Ngabdi, 2021)
This community service aims to improve the welfare of the community, especially in the coastal areas of Labuhan Hajj village who work as fishermen, as an area that is included in the category of underprivileged areas, this area needs touches that can improve the welfare of its people by optimizing the potential that exists in the village. namely seaweed and its sea products which are quite large. This century, named Kobe Molek, this time, how to cultivate the existing potential to make various culinary delights that can be liked by many people with various attractive forms, affordable prices and can be found in many places. One of the potentials of this area is processing sea rumpu into snacks that they like, having a distinctive taste, such as seaweed lunkhead, seaweed pilus cake, grass grass and so on, while ordinary fish is made of long-lasting shredded with a tantalizing taste and pamper the tongue of culinary lovers . as well as the form of packaging that makes consumers' eyes fixed and of course at a price that does not drain a lot of pockets. The village's huge potential requires high creativity so that it can be accepted by the community and able to compete among other entrepreneurs. This community creativity needs to be supported by training such as product processing, packaging and marketing and what is no less important is financial management.  This training is carried out in coordination with related agencies such as the social service, the trade office to be able to provide guidance and direction as well as provide assistance starting from training in production, packaging and sales. The container in the community called Kobe Molek is a container for fishermen's wives who are concerned about cultivating the potential of the village, namely seaweed and its fish products that process it into culinary according to the wishes of consumers. This product is marketed around the village and trying to be marketed through social media, such as Facebook, Instagram, whatshapp, with the hope that the products can be sold more widely and participate in exhibitions conducted by related agencies.